Barriers to Construction Health and Safety Self-regulation: A Scoping Case of Nigeria - Umeokafor Nnedinma (Civil Engineering Dimension, 2017)
This scoping study builds on the recent uncovering that in terms of health and safety (H&S), the Nigerian construction industry is self-regulated in various forms, not unregulated and that the size of company can further explain H&S self-regulation. Consequently, the barriers identified through literature review were assessed using questionnaires. Analysis of the data collected from construction practitioners in Nigeria shows that ‘economic factors’ mostly explains the barriers to construction H&S self-regulation. This is followed by the ‘ability to self-regulate’ and ‘lack of awareness’. Furthermore, the results show significant differences among small, medium and large construction contractors on seven factors of which include ‘normative case’ factors, ‘H&S is a duty’, ‘H&S is the right thing’ and ‘unfair H&S standards or legislation’. Although a scoping study, the study draws attention to the barriers to construction H&S self-regulation in Nigeria and demonstrates an alternative to state regulation of H&S.